Cities farming for the future : urban agriculture for green and productive cities - Veenhuizen, René van (RUAF Foundation : International Institute of Rural Reconstruction ; International Development Research Centre, 2006)
Urban agriculture is the growing of plants and the raising of animals for food and other uses, and related processing and marketing activities, within and around cities and towns. In the past few years, it has received increasing attention from development organizations and national and local authorities in developing countries. With its multiple functions, urban agriculture plays an important role in urban poverty alleviation and social inclusion, urban food security, urban waste management, and urban greening. Since 1999, partners of the International Network on Urban Agriculture and Food Security (RUAF Foundation) have been playing a crucial role in improving access to information on urban agriculture and in enhancing the capacities of local authorities, NGOs, farmer organizations, and other stakeholders regarding local participatory diagnosis and strategic action planning on urban agriculture. This book presents the state of the art in the development of sustainable urban agriculture, and will be primarily of interest to municipal authorities, NGOs, community-based organizations, governmental organizations, and other stakeholders and development practitioners in urban agriculture.